Every Teacher a Leaders : Developing the Needed Dispositions, Knowledge, and Skills for Teacher Leadership - Levin, Barbara B; Schrum, Lynne (Tounsand Oaks, California : Corwin, A SAGE Company, 2017)
"This practical handbook prepares teachers for leadership roles with specific how-tos for the essential skills they'll need most: running meetings, teaching colleagues, providing feedback, conducting needs assessments, delivering effective professional development, resolving conflicts, employing technology, and more. The book features well-tested content and activities, reflective writing prompts, scenarios for discussion, self-evalutations, two companion guides: one for teachers, and one for administrators"--Cove
Includes index
Keywords: School management and organization -- United States; Educational leadership -- United States